2022
DOI: 10.1166/jbt.2022.3144
|View full text |Cite
|
Sign up to set email alerts
|

miR-146 Relieves Acute Asthma via Decreasing Epidermal Growth Factor Receptor/Toll-Like Receptor 4 (EGFR/TLR4) and Enhancing Autophagy

Abstract: There is a close relationship between acute asthma and autophagy. In addition, some studies claim that miR-146 can regulate autophagy and participate in acute asthma. This study further explores the role of miR-146 in acute asthma and underlying mechanism. Twenty BALB/c mice were selected and randomly divided into two groups, the model group and the control group, each with 10 mice. Lung tissues, peripheral blood, alveolar lavage fluid, and primary lymphocytes were separated into miR-146 over expression group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Lung cancer treatment with NPs could be associated with induced ROS, leading to apoptosis and necrosis ( Nasrin et al, 2022 ). Nanoparticles can also downregulate the expression of Toll-like receptor 4, which is known as carcinogenesis in lung cancer cells and affects lung cancer treatment ( Wang et al, 2022 ). In addition, it was indicated that treatment of lung cancer cells with NPs downregulated VEGF, HIF-1α, IL-8, and Bcl-2 genes but increased the gene expression of p53 ( Huang et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer treatment with NPs could be associated with induced ROS, leading to apoptosis and necrosis ( Nasrin et al, 2022 ). Nanoparticles can also downregulate the expression of Toll-like receptor 4, which is known as carcinogenesis in lung cancer cells and affects lung cancer treatment ( Wang et al, 2022 ). In addition, it was indicated that treatment of lung cancer cells with NPs downregulated VEGF, HIF-1α, IL-8, and Bcl-2 genes but increased the gene expression of p53 ( Huang et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%